Virus deep sequencing: understanding the unknown - Rozado Aguirre, Zurine (2018)
Plant viruses are usually linked to plant or crop infection and disease, with many examples of viral infection causing social, environmental and economic damage in plants and crops described worldwide. Therefore, the choice of any particular management strategy which helps to avoid or reduce virus infection and disease in the field, needs to be specifically studied and evaluated according to the etiology of each pathogen, transmission and impact. Field samples were collected from carrot crops during the period 2014-2016 across different regions and countries and were tested using real-time Polymerase Chain Reaction (RT-qPCR). Results revealed high levels of viral infection and showed the elevated presence of previously undescribed viruses such as Carrot torrado virus1 (CaTV1) and Carrot closterovirus 1 (CtCV1). Higher levels of infection found in year-round cultivation fields also indicated that this type of practice, widely used in the UK, might be detrimental and act in favour of virus infection. Further studies identified Cow Parsley and Hogweed as possible virus reservoirs of the tested viruses and identified the aphid species Myzus persicae, as the vector responsible of CaTV1 transmission. Early detection of a pathogen from a field sample relies on the development and availability of a specific, sensitive and rapid diagnostic method. A RT-qPCR diagnostic assay has been developed and validated for the detection of CaTV1 according to the requirements established in the European Plant Protection Organization bulletin. Next Generation Sequencing (NGS) was used to study viral communities in carrots and a new viral sequence from the genus Carlavirus was identified in samples from the UK. By comparison with specific targeted diagnostics, this technique was shown to be a valuable approach for field surveillance and rapid detection of all the viruses present in a sample. The use of more modern and sophisticated techniques such as NGS, has led to the discovery of high numbers of new viruses with unknown impact. As with CaTV1, many viruses have been found to not cause any acute disease in the infected plants. However, in this study some asymptomatic viruses, recently identified using NGS, were found to be more abundant in herbicide resistant than in wild-type sensitive black grass plants. Although no relationship between the presence of these viruses in the plants and the development of herbicide resistance could be established, the effects of asymptomatic infections are discussed.